Development and application of a 200 kW ORC generator system for energy recovery in chemical processes. (September 2017) - Lee, Yuh-Ren; Liu, Li-Wei; Chang, Yun-Yuan; Hsieh, Jui-Ching
Abstract: Depending on heat source and heat sink conditions, an organic Rankine cycle (ORC) can be used to convert low temperature thermal energy (such as industrial waste heat, geothermal, biomass, and solar thermal energy) into electrical power. This research focuses on the development of an ORC with 200 kW power rating, which is intended to convert thermal energy into electricity for the chemical company in Taiwan. R134a is selected as the working fluid. The main components of the ORC consist of a working fluid pump, a shell-and-tube type evaporator, a shell-and-tube type super heater, a screw expander, an oil-vapor separator, and a shell-and-tube type condenser. This is the first commercially sized ORC (200 kW ) operating at a low temperature (82 ℃ ) to have been successfully developed in Taiwan, with all of the components also having been manufactured in Taiwan. The test results show that the net power output was 193.75 kW with a thermal efficiency of 4.701% for a water flow based heat source at a temperature of 81.5 ℃ and at a flow rate of 189 tons per hour . The ORC system has been running for more than 20, 600 hours ( Nov. 2014 to Apr. 2017 ) with a total power generation of more than 4, 248, 000 kWh without the occurrence of any faults.